Developing evidence-based recommendations surrounding training during and following pregnancy in elite athletes - Adams, W. M.; Anderson, T.; Post, E. G.; Christopher, S. M.; McKay, A. K. A.; Donaldson, A. T.; Galán-López, N.; Finnoff, J. T.; Carter, S.; Taylor, L. (International Journal of Sports Physiology and Performance, 2026)
The representation of females in sport and exercise-science literature remains limited, prompting focused efforts to expand the breadth of research in the field, particularly surrounding training and competition during and following pregnancy in elite athletes. Much of the existing literature on this topic provides little to no guidance for females, coaches, health-care personnel, and high-performance staff on how to most appropriately develop effective and healthy training programs during the perinatal period.